Trends in fertiliser use and efficiency in the Great Barrier Reef catchment area - Stephen E. Lewis; Cassandra S. James; Zoe T. Bainbridge; Aaron M. Davis; Adam Northey; Emma Lawrence; Rebecca Bartley (Journal of Environmental Management, 2026)

Disentangling effects of protection on seabed organic carbon and biodiversity in a rare highly protected mud-dominated MPA - Benjamin Harris; Tara Williams; Mara Fischer; Torsa Sengupta; Ceri Lewis; Adam Porter; Julie Hawkins; Zoe Roseby; Callum Roberts (Estuarine, Coastal and Shelf Science, 2026)

Dietary nitrate supplementation does not improve resistance exercise performance in resistance-trained women - Sydney N. Brennan; Justin M. Foster; Raymond T. Gerardo; Trevor J. Molnar; Ryan Tran; Christopher B. Sottile; Kyle S. Geppert; Michael Egiazarian; Abigail F. Ballhagen; Money Ghimire; John R. M. Renwick; Lewis A. Gough; et al. (European Journal of Applied Physiology, 2026)

The effect of Asparagopsis oil supplementation level on tissue residues and meat quality of Merino sheep fed high- or low-quality basal diets - Charlotte Adam; Emma Doyle; Jillian Dawson; Frances Cowley; Nigel Tomkins; Lewis Kahn; James Preston; Daniel Korir Sitienei; Matthew Tom Harrison; Benjamin W.B. Holman (Small Ruminant Research, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Combining environmental DNA and traditional sampling to assess the role of kelp aquaculture as an artificial habitat in Norway - Adam Jon Andrews; Hartvig Christie; Kim Præbel; Melissa Brandner; Ragnhild Grimm Torstensen; Larisa Lewis; Ragnhild Beck Hestness; Paul Ragnar Berg; Trine Bekkby; Kasper Hancke (Frontiers in Marine Science, 2025)
Kelp aquaculture is expanding rapidly in the temperate Atlantic, yet its ecological role as an artificial habitat remains poorly understood. This study assessed the biodiversity associated with wave-exposed kelp farms in coastal Norway using both environmental DNA (eDNA) and traditional sampling methods. Fish and invertebrate communities were surveyed at two kelp farms and compared to nearby natural kelp forests and pelagic control sites. Results from gill-net fishing, camera observations, and invertebrate sampling revealed lower species richness and abundance at kelp farms compared to natural habitats. eDNA analyses (12S and CO1 markers) showed few differences in community composition between sites, and no species were identified as significantly associated with kelp farms. Traditional sampling detected the presence of the amphipod Caprella mutica in the kelp farms, indicating that seaweed farmers can play roles in alien species spread. Overall, kelp farms supported distinct but less diverse communities than natural kelp forests, being more similar to pelagic control sites. Finally, eDNA provided limited insights compared to traditional methods. These findings suggest that kelp farms currently provide limited habitat provisioning in Norway, likely as a result of how and where kelp aquaculture is currently performed. We suggest the need for population-level assessments for species like Atlantic lumpfish ( Cyclopterus lumpus ) that commonly use kelp farms as habitats, and locally based assessments in collaboration with authorities to define nature-positive or -negative outcomes to balance ecological and economic goals in the growing seaweed aquaculture industries of the Atlantic.

Effects of environmental conditions on mate fidelity in a socially monogamous seabird - Sue Lewis; Adam Butler; Sarah Wanless; Mark A. Newell; Michael P. Harris; Sarah J. Burthe; Carrie M. Gunn; Richard J. Howells; Francis Daunt (Animal Behaviour, 2025)

Dietary exposure to hexafluoropropylene oxide dimer acid (HFPO-DA ammonium salt, GenX) alters hepatic sphingomyelin and phosphatidylcholine metabolism in Nile Tilapia (Oreochromis niloticus) - Amany Sultan; Isaac Konig; Adam D. Point; Victor Hugo Buttrós; Russell L. Lewis; Denina B.D. Simmons; Christopher J. Martyniuk (Aquatic Toxicology, 2025)

Advancing mussel-based monitoring: integrating litter and harmful algal bloom data into a multi-stressor assessment of England and Wales - Alexandra R. McGoran; Shamina Page; Adam Lewis; Adil Bakir; Jon Barry; Karl Dean; Josie Russell (Frontiers in Marine Science, 2025)
Effective monitoring is essential for decision makers to make informed choices to address pollution issues, including marine litter and microplastics which are subjects of increasing interest. Monitoring biota is essential for estimating the bioavailable fraction of litter in the environment and is a step towards understanding the risks associated with microplastics. The present study assessed the suitability of mussels as a sentinel species in a multi-stressor context. Mussels are already used as sentinel species for many contaminants, including harmful algal blooms, but to date there is no agreed sentinel species targeting microplastics. Mussels from seven locations on the English and Welsh coast were monitored for both microplastics and harmful algal biotoxins. Fluorescent and non-fluorescent microplastics were quantified. Over half (53%) of mussels contained microplastics. No geographical accumulation zones in microplastic abundance were identified at the sample locations with a mean contamination of 1.33 ± 3.04 (SD) items per individual (95% CI = 0.88–1.79) and 0.33 ± 0.71 items per g (wet weight) (95% CI = 0.23–0.44). Five groups of harmful algal toxins were screened within the study animals, with no quantifiable levels of any being present at the time of sampling for this study. However, four of the six sites were exposed to the Diarrhetic shellfish toxins earlier in the year, representing a prior exposure to harmful algal toxins. Research has shown that microplastic exposure alone does not always negatively impact organisms. But there is mounting evidence that microplastics may increase sensitivity and susceptibility to other stressors in the environment. Given the presence of both microplastics and algal neurotoxins in oceans around the world and the concern for multi-stressor impacts on the marine environment, it is proposed that multi-factor monitoring could provide insight into the true risk of microplastics as a contaminant vector and antagonistic pollutant. This evidence is urgently needed to support governments globally in creating mitigation strategies and monitoring the success of these interventions. The present study finds that mussels are a suitable sentinel species for this use, but ongoing research is needed to determine special and temporal variations.

Plastic pollution in mangrove ecosystems: A global meta-analysis - Katie Deakin; Adam Porter; Andrea Osorio Baquero; Ceri Lewis (Marine Pollution Bulletin, 2025)

Community-based mangrove restoration following a catastrophic hurricane in The Bahamas - Justin P. Lewis; Sean T. Giery; Keith A. Rossin; Kyle A. Rossin; Jordan R. Cissell; Michael K. Steinberg; Nina L. Sanchez; Aaron J. Adams; Craig A. Layman (Wetlands Ecology and Management, 2025)
Restoration of damaged coastal ecosystems is a component of broader conservation strategies. Hurricane Dorian (September 2019) was the worst natural disaster in the history of The Bahamas. This caused widespread societal and ecological damage, including destroying mangrove ecosystems—systems that provide numerous ecosystem services for the country. We first used satellite mapping to document mangrove destruction caused by Dorian. Second, several local, national, and international partners organized to spearhead community-based mangrove planting initiatives that resulted in more than 101,560 trees planted as of December 2024. We carried out a field experiment with the plantings to examine the effects of tree age (propagule vs. seedling), spacing design (clumped vs. spaced), and plant source (The Bahamas vs. Florida). Seedling survival was 4.5 × that of propagules—but at a greater time and financial cost—indicating that a combination of planting propagules and seedlings may be a preferred restoration approach. No effect of clumped vs. spaced distribution was found. This suggests other factors, e.g., nutrient limitation or hydroperiod, drive the success of plantings. Source effects (whether propagules were collected from, and grown to seedlings in, The Bahamas or Florida) influenced seedling survival and growth and had an influence similar in magnitude to local patch-scale environmental variation. The need for ecosystem restoration following Hurricane Dorian and the willingness of more than 2,000 community individuals to contribute made possible the scale and scope of this project. These findings will help guide this community-based initiative and it will inform similar restoration efforts in other regions.

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

Dose-response of Asparagopsis extract and diet quality effects enteric methane emissions for sheep fed high-forage diets - Charlotte Adam; Frances C. Cowley; Daniel Korir Sitienei; Nigel Tomkins; Lewis Kahn; James Preston; Emma Doyle (Small Ruminant Research, 2025)

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

A Review of Elite Athlete Evidence-Based Knowledge and Preparation for Competing in the Heat - Chris J. Esh; Sarah Carter; Natalia Galan-Lopez; Frederic Garrandes; Stephane Bermon; Paolo Emilio Adami; Sebastien Racinais; Lewis James; Trent Stellingwerff; William M. Adams; Bryna Chrismas; Christopher J. Stevens; et al. (Journal of Science in Sport and Exercise, 2024)
Elite athletes will compete in extreme heat more frequently as global land and sea temperatures increase, alongside more intense, frequent and longer duration heatwaves. Best practices to protect athlete health and performance during competition include heat acclimation/acclimatisation [(HA); i.e., long-term pre-competition preparation] complemented by pre-planned and practised cooling and hydration strategies (i.e., short-term interventions immediately before or during competition). This review explores elite athletes’ current behaviours and practices when preparing for competition in the heat and assesses the level of knowledge that has been exhibited by athletes and their practitioners in this space. Recommendations for future research, discussions of current best practices, and methods to improve translation of research into practice are provided. Available research focuses on small samples of elite endurance athletes during a selection of World Championship/Olympic/Paralympic events (~6% of competing athletes). While generally an increase in the adoption of evidence-based HA is seen chronologically from 2015 onwards, universal adoption is not seen. HA adoption is lowest in those who live/train in cold/temperate environments with cost and access to facilities/equipment being the most commonly reported barriers. Further research is required across the sporting landscape to fully characterise elite athlete behaviours and practices in these spaces. International federations and national governing bodies should continue their efforts to educate athletes and focus on regularly updated and reinvigorated release of evidence-based guidelines (in multiple germane languages) for competing in the heat, to increase the adoption of HA and other heat related best practice.

Sea surface microplastics in the Galapagos: Grab samples reveal high concentrations of particles <200 μm in size - Katie Deakin; Georgie Savage; Jen S. Jones; Adam Porter; Juan Pablo Muñoz-Pérez; David Santillo; Ceri Lewis (Science of The Total Environment, 2024)

Plastic pollution transcends marine protected area boundaries in the eastern tropical and south-eastern Pacific - Zara L.R. Botterell; Francisca Ribeiro; Daniela Alarcón-Ruales; Eliana Alfaro; Joanna Alfaro-Shigueto; Nicola Allan; Nicole Becerra; Laura Braunholtz; Susana Cardenas-Diaz; Diamela de Veer; Gabriela Escobar-Sanchez; Maria Virginia Gabela-Flores; et al. (Marine Pollution Bulletin, 2024)

Understanding pharmaceutical exposure and the potential for effects in marine biota: A survey of bonefish (Albula vulpes) across the Caribbean Basin - N.A. Castillo; W.R. James; R.O. Santos; R. Rezek; D. Cerveny; R.E. Boucek; A.J. Adams; T. Goldberg; L. Campbell; A.U. Perez; J.J. Schmitter-Soto; J.P. Lewis; et al. (Chemosphere, 2024)

Illegal incidents and violations related to Atlantic salmon fishing in Newfoundland and Labrador, Canada, during 2001–2020 - Travis E. Van Leeuwen; David Cote; Sarah J. Lehnert; Sky Ann Lewis; Daryl Walsh; Kerry Bungay; Nicholas I. Kelly; Jason McGinn; Blair Adams; J. Brian Dempson (Fisheries Management and Ecology, 2024)
Resource user compliance is a key element in effective fisheries management. Herein, we examine two decades of enforcement records pertaining to Atlantic salmon from Newfoundland and Labrador, Canada. Illegal incidents were negatively correlated with the number of licensed anglers but not salmon abundance. Over two decades, illegal incidents declined by 66%, even after correcting for the positive relationship between enforcement effort and illegal incidents. This decline was primarily driven by a 67% reduction in netting and jigging‐related violations, which were likely to impose the highest levels of mortality on adult salmon among violations examined. Additionally, illegal incidents and violation types did not increase as a result of management changes. While Newfoundland and Labrador remains one of the last strongholds for Atlantic salmon, we encourage other jurisdictions to monitor fisheries compliance to better understand the social‐ecological landscape that is crucial to supporting healthy fisheries.

Ocean Color Image Sequences Reveal Diurnal Changes in Water Column Stability Driven by Air–Sea Interactions - Jason K. Jolliff; Travis A. Smith; Sherwin Ladner; Ewa Jarosz; Mark David Lewis; Stephanie Anderson; Sean McCarthy; Adam Lawson (Journal of Marine Science and Engineering, 2023)
The southward propagation of cold-air frontal boundaries into the Gulf of Mexico region initiates a cascade of coupled air–sea processes that manifests along the coastlines as an apparent brightness anomaly in the ocean color signals. Our hypothesis is that the color anomaly is largely due to the turbulent resuspension of sedimentary particles. Initially, there is significant wind-driven ocean turbulence as the frontal boundary passes, followed by the potential for sustained convective instability due to significant heat losses from the ocean surface. These cold front events occur during boreal autumn, winter, and into early spring, and the latter episodes occur in the context of the seasonally recurring thermal stratification of shelf waters. Here, we show that as stratification reasserts thermal stability in the waning days of a cold front episode, daily to hourly ocean color patterns are temporally coherent with the air–sea heat flux changes and the resulting impact on water column stability. Concomitant results from a nested, data-assimilative, and two-way coupled ocean-atmosphere numerical modeling system provides both corroboration and insight into how surface air–sea fluxes and in-water turbulent mixing manifest as hourly changes in apparent surface water turbidity due to the potential excitation and settling of reflective particles. A simple model of particle mixing and settling driven by the simulated turbulence mimics patterns seen in the satellite image sequences. This study offers a preview of potential application areas that may emerge following the launch of a dedicated ocean color geostationary sensor.

Top ten priorities for global saltmarsh restoration, conservation and ecosystem service research - Julien Pétillon; Emma McKinley; Meghan Alexander; Janine B. Adams; Christine Angelini; Thorsten Balke; John N. Griffin; Tjeerd Bouma; Sally Hacker; Qiang He; Marc J.S. Hensel; Carles Ibáñez; et al. (Science of The Total Environment, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Fruit availability and human disturbance influence forest elephant group size - Amelia C. Meier; Stephanie Bourgeois; Evan Adams; Hugues Bikang; Liam Jasperse-Sjolander; Matthew Lewis; Juliana Masseloux; Dana J. Morin; John R. Poulsen (Animal Behaviour, 2023)

Immediate and delayed effects of a heatwave and Prorocentrum lima ((Ehrenberg) Stein 1878) bloom on the toxin accumulation, physiology, and survival of the oyster Magallana gigas (Thunberg, 1793) - Ellen Grace M. Funesto; Adam M. Lewis; Andrew D. Turner; Tom C. Cameron; Michael Steinke (Science of The Total Environment, 2023)

Gill microbiomes accurately predict the geographic origin of bonefish (Albula vulpes) when combined with machine learning models - Lewis J. Campbell; Nicholas A. Castillo; Christopher D. Dunn; Shimana M. Bose; Addiel U. Perez; Juan J. Schmitter-Soto; Sahar Mejri; Ross E. Boucek; Rolando Santos Corujo; Aaron J. Adams; Jennifer S. Rehage; Tony L. Goldberg (Environmental Biology of Fishes, 2023)

A comprehensive phylogeny and revised taxonomy illuminate the origin and diversification of the global radiation of Papilio (Lepidoptera: Papilionidae) - Fabien L. Condamine; Rémi Allio; Eliette L. Reboud; Julian R. Dupuis; Emmanuel F.A. Toussaint; Nathan Mazet; Shao-Ji Hu; Delano S. Lewis; Krushnamegh Kunte; Adam M. Cotton; Felix A.H. Sperling (Molecular Phylogenetics and Evolution, 2023)

A snapshot of online wildlife trade: Australian e-commerce trade of native and non-native pets - Adam Toomes; Stephanie Moncayo; Oliver C. Stringham; Charlotte Lassaline; Lisa Wood; Mariah Millington; Charlotte Drake; Charlotte Jense; Ashley Allen; Katherine G.W. Hill; Pablo García-Díaz; Lewis Mitchell; et al. (Biological Conservation, 2023)

Automated Atmospheric Correction of Nanosatellites Using Coincident Ocean Color Radiometer Data - Sean McCarthy; Summer Crawford; Christopher Wood; Mark D. Lewis; Jason K. Jolliff; Paul Martinolich; Sherwin Ladner; Adam Lawson; Marcos Montes (Journal of Marine Science and Engineering, 2023)
Here we present a machine-learning-based method for utilizing traditional ocean-viewing satellites to perform automated atmospheric correction of nanosatellite data. These sensor convolution techniques are required because nanosatellites do not usually possess the wavelength combinations required to atmospherically correct upwelling radiance data for oceanographic applications; however, nanosatellites do provide superior ground-viewing spatial resolution (~3 m). Coincident multispectral data from the Suomi National Polar-Orbiting Partnership Visible Infrared Imaging Radiometer Suite (Suomi NPP VIIRS; referred to herein as “VIIRS”) were used to remove atmospheric contamination at each of the nanosatellite’s visible wavelengths to yield an estimate of spectral water-leaving radiance [Lw(l)], which is the basis for surface ocean optical products. Machine learning (ML) algorithms (KNN, decision tree regressors) were applied to determine relationships between Lw and top-of-atmosphere (Lt)/Rayleigh (Lr) radiances within VIIRS training data, and then applied to test cases for (1) the Marine Optical Buoy (MOBY) in Hawaii and (2) the AErosol RObotic Network Ocean Color (AERONET-OC), Venice, Italy. For the test cases examined, ML-based methods appeared to improve statistical results when compared to alternative dark spectrum fitting (DSF) methods. The results suggest that ML-based sensor convolution techniques offer a viable path forward for the oceanographic application of nanosatellite data streams.

Correction to: Viruses of Atlantic Bonefsh (Albula vulpes) in Florida and the Caribbean show geographic patterns consistent with population declines - Lewis J. Campbell; Nicholas A. Castillo; Christopher D. Dunn; Addiel Perez; Juan J. Schmitter-Soto; Sahar C. Mejri; Ross E. Boucek; Rolando Santos Corujo; Aaron J. Adams; Jennifer S. Rehage; Tony L. Goldberg (Environmental Biology of Fishes, 2023)

Bone appétit: DNA metabarcoding as a non-lethal alternative to morphological dietary assessment in Atlantic bonefish (Albula vulpes) - Lewis J. Campbell; Nicholas A. Castillo; Jonathan Shenker; Leah A. Owens; Rolando O. Santos; Aaron J. Adams; Jennifer S. Rehage; Kate E. Denton; Tony L. Goldberg (Environmental Biology of Fishes, 2023)

Viruses of Atlantic Bonefish (Albula vulpes) in Florida and the Caribbean show geographic patterns consistent with population declines - Lewis J. Campbell; Nicholas A. Castillo; Christopher D. Dunn; Addiel Perez; Juan J. Schmitter-Soto; Sahar C. Mejri; Ross E. Boucek; Rolando Santos Corujo; Aaron J. Adams; Jennifer S. Rehage; Tony L. Goldberg (Environmental Biology of Fishes, 2023)

Uptake of microplastics by marine worms depends on feeding mode and particle shape but not exposure time - Adam Porter; Dan Barber; Catherine Hobbs; John Love; Ann L. Power; Adil Bakir; Tamara S. Galloway; Ceri Lewis (Science of The Total Environment, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Characterizing spatial and temporal variation in stable hydrogen isotopes (δ2H) between two distinct lentic freshwater food webs - Michael C. Cavallaro; Chantel I. Michelson; Tyler L. Lewis; Adam DuBour; Mark Lindberg; Keith A. Hobson; Robert G. Clark (Aquatic Sciences, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

An introduction to decision science for conservation - Victoria Hemming; Abbey E. Camaclang; Megan S. Adams; Mark Burgman; Katherine Carbeck; Josie Carwardine; Iadine Chadès; Lia Chalifour; Sarah J. Converse; Lindsay N. K. Davidson; Georgia E. Garrard; Riley Finn; et al. (Conservation Biology, 2022)
Biodiversity conservation decisions are difficult, especially when they involve differing values, complex multidimensional objectives, scarce resources, urgency, and considerable uncertainty. Decision science embodies a theory about how to make difficult decisions and an extensive array of frameworks and tools that make that theory practical. We sought to improve conceptual clarity and practical application of decision science to help decision makers apply decision science to conservation problems. We addressed barriers to the uptake of decision science, including a lack of training and awareness of decision science; confusion over common terminology and which tools and frameworks to apply; and the mistaken impression that applying decision science must be time consuming, expensive, and complex. To aid in navigating the extensive and disparate decision science literature, we clarify meaning of common terms: decision science , decision theory , decision analysis , structured decision‐making , and decision‐support tools . Applying decision science does not have to be complex or time consuming; rather, it begins with knowing how to think through the components of a decision utilizing decision analysis (i.e., define the problem, elicit objectives, develop alternatives, estimate consequences, and perform trade‐offs). This is best achieved by applying a rapid‐prototyping approach. At each step, decision‐support tools can provide additional insight and clarity, whereas decision‐support frameworks (e.g., priority threat management and systematic conservation planning) can aid navigation of multiple steps of a decision analysis for particular contexts. We summarize key decision‐support frameworks and tools and describe to which step of a decision analysis, and to which contexts, each is most useful to apply. Our introduction to decision science will aid in contextualizing current approaches and new developments, and help decision makers begin to apply decision science to conservation problems.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

How Do African-American Community Members’ Perceptions About Environmental Risks of Breast Cancer Compare with the Current State of the Science? - Brooks Yelton; Jamie R. Lead; Swann Arp Adams; Heather M. Brandt; Shibani Kulkarni; Kaleea R. Lewis; Delores Fedrick; John R. Ureda; Daniela B. Friedman (Journal of Cancer Education, 2021)

Wealth and urbanization shape medium and large terrestrial mammal communities - Seth B. Magle; Mason Fidino; Heather A. Sander; Adam T. Rohnke; Kelli L. Larson; Travis Gallo; Cria A. M. Kay; Elizabeth W. Lehrer; Maureen H. Murray; Solny A. Adalsteinsson; Adam A. Ahlers; Whitney J. B. Anthonysamy; et al. (Global Change Biology, 2021)
Urban biodiversity provides critical ecosystem services and is a key component to environmentally and socially sustainable cities. However, biodiversity varies greatly within and among cities, leading to human communities with changing and unequal experiences with nature. The “luxury effect,” a hypothesis that predicts a positive correlation between wealth, typically measured by per capita income, and species richness may be one indication of these inequities. While the luxury effect is well studied for some taxa, it has rarely been investigated for mammals, which provide unique ecosystem services (e.g., biological pest control) and exhibit significant potential for negative human–wildlife interactions (e.g., nuisances or conflicts). We analyzed a large dataset of mammal detections across 20 North American cities to test whether the luxury effect is consistent for medium‐ to large‐sized terrestrial mammals across diverse urban contexts. Overall, support for the luxury effect, as indicated by per capita income, was inconsistent; we found evidence of a luxury effect in approximately half of our study cities. Species richness was, however, highly and negatively correlated with urban intensity in most cities. We thus suggest that economic factors play an important role in shaping urban mammal communities for some cities and species, but that the strongest driver of urban mammal diversity is urban intensity. To better understand the complexity of urban ecosystems, ecologists and social scientists must consider the social and political factors that drive inequitable human experiences with nature in cities.

A guide to using the internet to monitor and quantify the wildlife trade - Oliver C. Stringham; Adam Toomes; Aurelie M. Kanishka; Lewis Mitchell; Sarah Heinrich; Joshua V. Ross; Phillip Cassey (Conservation Biology, 2021)
The unrivaled growth in e‐commerce of animals and plants presents an unprecedented opportunity to monitor wildlife trade to inform conservation, biosecurity, and law enforcement. Using the internet to quantify the scale of the wildlife trade (volume and frequency) is a relatively recent and rapidly developing approach that lacks an accessible framework for locating relevant websites and collecting data. We produced an accessible guide for internet‐based wildlife trade surveillance. We detailed a repeatable method involving a systematic internet search, with search engines, to locate relevant websites and content. For data collection, we highlight web‐scraping technology as an efficient way to collect data in an automated fashion at regularly timed intervals. Our guide is applicable to the multitude of trade‐based contexts because researchers can tailor search keywords for specific taxa or derived products and locations of interest. We provide information for working with the diversity of websites used in wildlife trade. For example, to locate relevant content on social media (e.g., posts or groups), each social media platform should be examined individually via the site's internal search engine. A key advantage of using the internet to study wildlife trade is the relative ease of access to an increasing amount of trade‐related data. However, not all wildlife trade occurs online and it may occur on unobservable sections of the internet.

Tropicalization of temperate ecosystems in North America: The northward range expansion of tropical organisms in response to warming winter temperatures - Michael J. Osland; Philip W. Stevens; Margaret M. Lamont; Richard C. Brusca; Kristen M. Hart; J. Hardin Waddle; Catherine A. Langtimm; Caroline M. Williams; Barry D. Keim; Adam J. Terando; Eric A. Reyier; Katie E. Marshall; et al. (Global Change Biology, 2021)
Tropicalization is a term used to describe the transformation of temperate ecosystems by poleward‐moving tropical organisms in response to warming temperatures. In North America, decreases in the frequency and intensity of extreme winter cold events are expected to allow the poleward range expansion of many cold‐sensitive tropical organisms, sometimes at the expense of temperate organisms. Although ecologists have long noted the critical ecological role of winter cold temperature extremes in tropical–temperate transition zones, the ecological effects of extreme cold events have been understudied, and the influence of warming winter temperatures has too often been left out of climate change vulnerability assessments. Here, we examine the influence of extreme cold events on the northward range limits of a diverse group of tropical organisms, including terrestrial plants, coastal wetland plants, coastal fishes, sea turtles, terrestrial reptiles, amphibians, manatees, and insects. For these organisms, extreme cold events can lead to major physiological damage or landscape‐scale mass mortality. Conversely, the absence of extreme cold events can foster population growth, range expansion, and ecological regime shifts. We discuss the effects of warming winters on species and ecosystems in tropical–temperate transition zones. In the 21st century, climate change‐induced decreases in the frequency and intensity of extreme cold events are expected to facilitate the poleward range expansion of many tropical species. Our review highlights critical knowledge gaps for advancing understanding of the ecological implications of the tropicalization of temperate ecosystems in North America.

The Influence of the Toxin-Producing Dinoflagellate, Alexandrium catenella (1119/27), on the Survival and Reproduction of the Marine Copepod, Acartia tonsa, During Prolonged Exposure - Ali H. Abdulhussain; Kathryn B. Cook; Andrew D. Turner; Adam M. Lewis; Thomas S. Bibby; Daniel J. Mayor (Frontiers in Marine Science, 2021)
Copepods can feed on, and may regulate, the blooms of harmful algae (HA), and may also facilitate dinoflagellate blooms by inducing toxin production and through selective grazing. However, exposure to HA may also cause mortality and reproductive impairment in copepods, with detrimental effects at the population-scale. Here we present the toxin profile of the dinoflagellate, Alexandrium catenella (formerly Alexandrium tamarense ), and examine how it affects the survival and reproduction of the cosmopolitan marine copepod, Acartia tonsa . Healthy adult copepods were exposed to mono-specific diets of toxic and non-toxic strains of A. catenella (1119/27 and 1119/19, respectively) and non-toxic Rhodomonas sp. for 10 days alongside unfed controls to examine how their survival was influenced by likely HA bloom conditions. Additional 2-day experiments examined how their egg production rate and hatching success were affected by food deprivation, toxic A. catenella , a non-toxic alternative and a mixture of toxic and non-toxic prey, at high and low concentrations. Survival of A. tonsa declined over the 10-day experiment in all treatments but was not significantly lower in the toxic A. catenella treatment; mortality was only significantly enhanced in the unfed animals, which showed 100% mortality after 9 days. Egg production rates and hatching success from females in the unfed and toxic A. catenella treatments were all significantly lower than values observed in females fed Rhodomonas sp. or non-toxic A. catenella . Animals offered 1,000 μg C L –1 of Rhodomonas sp. and a 50:50 mixture of toxic A. catenella and Rhodomonas sp. produced significantly more eggs than animals fed toxic A. catenella alone. These results were not apparent at prey concentrations of 100 μg C L –1 . The percentages of eggs to successfully hatch from females offered mono-specific diets of toxic A. catenella were always close to zero. Collectively, our results indicate that adult female A. tonsa can acquire sufficient energy from toxic A. catenella to survive, but suffer reproductive impairment when feeding on this prey alone.

Fruits, vegetables, and health: A comprehensive narrative, umbrella review of the science and recommendations for enhanced public policy to improve intake - Taylor C. Wallace; Regan L. Bailey; Jeffrey B. Blumberg; Britt Burton-Freeman; C-y. Oliver Chen; Kristi M. Crowe-White; Adam Drewnowski; Shirin Hooshmand; Elizabeth Johnson; Richard Lewis; Robert Murray; Sue A. Shapses; et al. (Critical Reviews in Food Science and Nutrition, 2020)

Bacterial communities on the gills of bonefish (Albula vulpes) in the Florida Keys and The Bahamas show spatial structure and differential abundance of disease-associated bacteria - Christopher D. Dunn; Lewis J. Campbell; Elizabeth M. Wallace; Andy J. Danylchuk; Steven J. Cooke; Aaron D. Shultz; Brooke D. Black; Jacob W. Brownscombe; Lucas P. Griffin; David P. Philipp; Aaron J. Adams; Tony L. Goldberg (Marine Biology, 2020)

Resilience of the Copepod Oithona similis to Climatic Variability: Egg Production, Mortality, and Vertical Habitat Partitioning - Louise Elisabeth Cornwell; Elaine S. Fileman; John T. Bruun; Andrew Garwood Hirst; Glen Adam Tarran; Helen S. Findlay; Ceri Lewis; Timothy James Smyth; A. J. McEvoy; A. Atkinson (Frontiers in Marine Science, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Leveraging linkage evidence to identify low-frequency and rare variants on 16p13 associated with blood pressure using TOPMed whole genome sequencing data - Karen Y. He; Xiaoyin Li; Tanika N. Kelly; Jingjing Liang; Brian E. Cade; Themistocles L. Assimes; Lewis C. Becker; Amber L. Beitelshees; Adam P. Bress; Yen-Pei Christy Chang; Yii-Der Ida Chen; Paul S. de Vries; et al. (Human Genetics, 2019)

Measuring site fidelity and homesite-to-pre-spawning site connectivity of bonefish (Albula vulpes): using mark-recapture to inform habitat conservation - R. E. Boucek; J. P. Lewis; B. D. Stewart; Z. R. Jud; E. Carey; A. J. Adams (Environmental Biology of Fishes, 2019)

Behavioral observations of bonefish (Albula vulpes) during prespawning aggregations in the Bahamas: clues to identifying spawning sites that can drive broader conservation efforts - Andy J. Danylchuk; Justin Lewis; Zack Jud; Jonathan Shenker; Aaron Adams (Environmental Biology of Fishes, 2019)

Seasonal and spatial changes in sex hormone levels and oocyte development of bonefish (Albula vulpes) - Cameron Luck; Sahar Mejri; Justin Lewis; Paul S. Wills; Marty Riche; Jonathan Shenker; Aaron Adams; Matthew J. Ajemian (Environmental Biology of Fishes, 2019)

Identifying pre-spawning aggregation sites for bonefish (Albula vulpes) in the Bahamas to inform habitat protection and species conservation - Aaron J. Adams; Jonathan M. Shenker; Zachary R. Jud; Justin P. Lewis; Eric Carey; Andy J. Danylchuk (Environmental Biology of Fishes, 2019)

Recent multivariate changes in the North Atlantic climate system, with a focus on 2005–2016 - Jon Robson; Rowan T. Sutton; Alex Archibald; Fenwick Cooper; Matthew Christensen; Lesley J. Gray; N. Penny Holliday; Claire Macintosh; Malcolm McMillan; Ben Moat; Maria Russo; Rachel Tilling; et al. (International Journal of Climatology, 2018)
Major changes are occurring across the North Atlantic climate system, including in the atmosphere, ocean and cryosphere, and many observed changes are unprecedented in instrumental records. As the changes in the North Atlantic directly affect the climate and air quality of the surrounding continents, it is important to fully understand how and why the changes are taking place, not least to predict how the region will change in the future. To this end, this article characterizes the recent observed changes in the North Atlantic region, especially in the period 2005–2016, across many different aspects of the system including: atmospheric circulation; atmospheric composition; clouds and aerosols; ocean circulation and properties; and the cryosphere. Recent changes include: an increase in the speed of the North Atlantic jet stream in winter; a southward shift in the North Atlantic jet stream in summer, associated with a weakening summer North Atlantic Oscillation; increases in ozone and methane; increases in net absorbed radiation in the mid‐latitude western Atlantic, linked to an increase in the abundance of high level clouds and a reduction in low level clouds; cooling of sea surface temperatures in the North Atlantic subpolar gyre, concomitant with increases in the western subtropical gyre, and a decline in the Atlantic Ocean's overturning circulation; a decline in Atlantic sector Arctic sea ice and rapid melting of the Greenland Ice Sheet. There are many interactions between these changes, but these interactions are poorly understood. This article concludes by highlighting some of the key outstanding questions.

The initial hours of post-excision light are critical for adventitious root regeneration from Arabidopsis thaliana (L.) Heynh. cotyledon explants - M. Blair Nameth; Travis L. Goron; Stephen J. Dinka; Adam D. Morris; Jenny English; Dorrett Lewis; Rosalinda Oro; Manish N. Raizada (In Vitro Cellular & Developmental Biology - Plant, 2018)

Combining abundance and performance data reveals how temperature regulates coastal occurrences and activity of a roaming apex predator - Nicholas L. Payne; Carl G. Meyer; James A. Smith; Jonathan D. R. Houghton; Adam Barnett; Bonnie J. Holmes; Itsumi Nakamura; Yannis P. Papastamatiou; Mark A. Royer; Daniel M. Coffey; James M. Anderson; Melanie R. Hutchinson; et al. (Global Change Biology, 2018)
The redistribution of species has emerged as one of the most pervasive impacts of anthropogenic climate warming, and presents many societal challenges. Understanding how temperature regulates species distributions is particularly important for mobile marine fauna such as sharks given their seemingly rapid responses to warming, and the socio‐political implications of human encounters with some dangerous species. The predictability of species distributions can potentially be improved by accounting for temperature's influence on performance, an elusive relationship for most large animals. We combined multi‐decadal catch data and bio‐logging to show that coastal abundance and swimming performance of tiger sharks Galeocerdo cuvier are both highest at ~22°C, suggesting thermal constraints on performance may regulate this species' distribution. Tiger sharks are responsible for a large proportion of shark bites on humans, and a focus of controversial control measures in several countries. The combination of distribution and performance data moves towards a mechanistic understanding of tiger shark's thermal niche, and delivers a simple yet powerful indicator for predicting the location and timing of their occurrences throughout coastlines. For example, tiger sharks are mostly caught at Australia's popular New South Wales beaches (i.e. near Sydney) in the warmest months, but our data suggest similar abundances will occur in winter and summer if annual sea surface temperatures increase by a further 1–2°C.

Inhibition of the receptor for advanced glycation end-products (RAGE) protects from secondhand smoke (SHS)-induced intrauterine growth restriction IUGR in mice - Joshua B. Lewis; Camilo Mejia; Clinton Jordan; Troy D. Monson; Jared S. Bodine; Todd M. Dunaway; Kaleb M. Egbert; Adam L. Lewis; Tanner J. Wright; K. Connor Ogden; Dallin S. Broberg; Parker D. Hall; et al. (Cell and Tissue Research, 2017)

Gulf War illness (GWI) as a neuroimmune disease - Apostolos P. Georgopoulos; Lisa M. James; Adam F. Carpenter; Brian E. Engdahl; Arthur C. Leuthold; Scott M. Lewis (Experimental Brain Research, 2017)

Subcortical brain atrophy in Gulf War Illness - Peka Christova; Lisa M. James; Brian E. Engdahl; Scott M. Lewis; Adam F. Carpenter; Apostolos P. Georgopoulos (Experimental Brain Research, 2017)

Neuromuscular adaptations to sprint interval training and the effect of mammalian omega-3 fatty acid supplementation - Evan J. H. Lewis; Frédéric Stucky; Peter W. Radonic; Adam H. Metherel; Thomas M. S. Wolever; Greg D. Wells (European Journal of Applied Physiology, 2017)

Trophic dynamics of shrinking Subarctic lakes: naturally eutrophic waters impart resilience to rising nutrient and major ion concentrations - Tyler L. Lewis; Patricia J. Heglund; Mark S. Lindberg; Joel A. Schmutz; Joshua H. Schmidt; Adam J. Dubour; Jennifer Rover; Mark R. Bertram (Oecologia, 2016)

Testosterone enables growth and hypertrophy in fusion impaired myoblasts that display myotube atrophy: deciphering the role of androgen and IGF-I receptors - David C. Hughes; Claire E. Stewart; Nicholas Sculthorpe; Hannah F. Dugdale; Farzad Yousefian; Mark P. Lewis; Adam P. Sharples (Biogerontology, 2016)

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Population demographics of American eels Anguilla rostrata in two Arkansas, U.S.A., catchments that drain into the Gulf of Mexico - C. A. Cox; J. W. Quinn; L. C. Lewis; S. R. Adams; G. L. Adams (Journal of Fish Biology, 2016)
The goal of this study was to compare American eel Anguilla rostrata life history in two inland river systems in Arkansas, U.S.A., that ultimately discharge into the Gulf of Mexico via the Mississippi River and the Red‐Atchafalaya catchments. From 21 June 2011 to 24 April 2014, 238 yellow‐phase A. rostrata were captured in the middle Ouachita River and tributaries using boat electrofishing and 39 in the lower White River using multiple sampling gears. Most of them were caught downstream of dams in both basins (61%). Medium‐sized A. rostrata ranging from 225 to 350 mm total length ( L T ) were the most abundant size group in the Ouachita River basin, but they were absent from the White River. Mean L T at age 4 years ( i.e. youngest shared age) was 150 mm greater for the White River than the Ouachita River basin. Anguilla rostrata appeared to have a greater initial L T ( i.e. minimum size upon arrival) in the White River that allowed them to reach a gonado‐somatic index ( I G ) of 1·5 up to 4 years earlier, and downstream migration appeared to occur 5 years earlier at 100 mm greater L T ; these differences may be related to increased river fragmentation by dams in the Ouachita River basin. Growth and maturation of A. rostrata in this study were more similar to southern populations along the Atlantic coast than other inland populations. Adult swimbladder nematodes Anguillicoloides crassus were not present in any of the 214 swimbladders inspected. Gulf of Mexico catchments may be valuable production areas for A. rostrata and data from these systems should be considered as range‐wide protection and management plans are being developed.

Evaluating the performance of selection scans to detect selective sweeps in domestic dogs - Florencia Schlamp; Julian van der Made; Rebecca Stambler; Lewis Chesebrough; Adam R. Boyko; Philipp W. Messer (Molecular Ecology, 2016)
Selective breeding of dogs has resulted in repeated artificial selection on breed‐specific morphological phenotypes. A number of quantitative trait loci associated with these phenotypes have been identified in genetic mapping studies. We analysed the population genomic signatures observed around the causal mutations for 12 of these loci in 25 dog breeds, for which we genotyped 25 individuals in each breed. By measuring the population frequencies of the causal mutations in each breed, we identified those breeds in which specific mutations most likely experienced positive selection. These instances were then used as positive controls for assessing the performance of popular statistics to detect selection from population genomic data. We found that artificial selection during dog domestication has left characteristic signatures in the haplotype and nucleotide polymorphism patterns around selected loci that can be detected in the genotype data from a single population sample. However, the sensitivity and accuracy at which such signatures were detected varied widely between loci, the particular statistic used and the choice of analysis parameters. We observed examples of both hard and soft selective sweeps and detected strong selective events that removed genetic diversity almost entirely over regions >10 Mbp. Our study demonstrates the power and limitations of selection scans in populations with high levels of linkage disequilibrium due to severe founder effects and recent population bottlenecks.

The effects of height and BMI on prostate cancer incidence and mortality: a Mendelian randomization study in 20,848 cases and 20,214 controls from the PRACTICAL consortium - Neil M. Davies; Tom R. Gaunt; Sarah J. Lewis; Jeff Holly; Jenny L. Donovan; Freddie C. Hamdy; John P. Kemp; Rosalind Eeles; Doug Easton; Zsofia Kote-Jarai; Ali Amin Al Olama; Sara Benlloch; et al. (Cancer Causes & Control, 2015)

The assumption of radon-induced cancer risk - Krzysztof W. Fornalski; Rod Adams; Wade Allison; Leslie E. Corrice; Jerry M. Cuttler; Chris Davey; Ludwik Dobrzyński; Vincent J. Esposito; Ludwig E. Feinendegen; Leo S. Gomez; Patricia Lewis; Jeffrey Mahn; et al. (Cancer Causes & Control, 2015)

A mutant (‘lab strain’) of the hyperthermophilic archaeon Pyrococcus furiosus, lacking flagella, has unusual growth physiology - Derrick L. Lewis; Jaspreet S. Notey; Sanjeev K. Chandrayan; Andrew J. Loder; Gina L. Lipscomb; Michael W. W. Adams; Robert M. Kelly (Extremophiles, 2015)

The 2011–2016 Transdisciplinary Research on Energetics and Cancer (TREC) Initiative: Rationale and Design - Ruth E. Patterson; Graham A. Colditz; Frank B. Hu; Kathryn H. Schmitz; Rexford S. Ahima; Ross C. Brownson; Kenneth R. Carson; Jorge E. Chavarro; Lewis A. Chodosh; Sarah Gehlert; Jeff Gill; Karen Glanz; et al. (Cancer Causes & Control, 2013)

Forest Management, Engineering, and Operations / Global Competency and Issues in Contemporary Education - Finto Antony; Lewis Jordan; Laurie Schimleck; Richard Daniels; Rapeepan Kantavichai; Lara Hansen; Jessica Hitt; William Hubbard; Gwendolyn Boyd; Ryan Boyles; Heather Dinon; Joshua Idassi; et al. (Journal of Forestry, 2011)
31Maps depicting spatial variation in wood properties are important for forest product industries as they aid decision making regarding raw material procurement, can assist in product categorization and help improve utilization. Loblolly pine is an important commercial species grown throughout the southern Unites States of America (USA). Wood Quality Consortium (WQC)—a joint collaboration between the University of Georgia, USDA Forest Service and industries—was established in 1999 with the objective of characterizing wood property variation of plantation grown loblolly pine. Data on wood specific gravity (SG), modulus of elasticity (MOE) and modulus of rupture (MOR) collected by the WQC was utilized in this study. Maps showing spatial variation in SG at different stand ages and SG, MOE and MOR at different heights within a tree were developed using appropriate spatial prediction methods (kriging). The geographical variation of these wood properties across southeastern USA was demonstrated here.

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.

Mapping Cropping Practices Using MODIS Time Series: Harnessing the Data Explosion - Peter Tan; Leo Lymburner; Medhavy Thankappan; Adam Lewis (Journal of the Indian Society of Remote Sensing, 2011)

Structural abnormalities in the cortex of the rTg4510 mouse model of tauopathy: a light and electron microscopy study - Adam E. Ludvigson; Jennifer I. Luebke; Jada Lewis; Alan Peters (Brain Structure and Function, 2011)

Development of co-selected single nucleotide polymorphisms in the viral promoter precedes the onset of human immunodeficiency virus type 1-associated neurocognitive impairment - Luna Li; Benjamas Aiamkitsumrit; Vanessa Pirrone; Michael R. Nonnemacher; Adam Wojno; Shendra Passic; Katherine Flaig; Evelyn Kilareski; Brandon Blakey; Jade Ku; Nirzari Parikh; Rushabh Shah; et al. (Journal of NeuroVirology, 2011)

Electrocardiographic Predictors of Adverse Cardiovascular Events in Suspected Poisoning - Alex F. Manini; Lewis S. Nelson; Adam H. Skolnick; William Slater; Robert S. Hoffman (Journal of Medical Toxicology, 2010)

Assessing Condition-dependence of Male Flash Signals in Photinus Fireflies - Evelyn K. Sharkey; Adam South; Paul R. Moosman; Christopher K. Cratsley; Sara M. Lewis (Journal of Insect Behavior, 2010)

Expression and functional analysis of the WAP four disulfide core domain 1 gene in human melanoma - Suhu Liu; Paul Howell; Suping Ren; Oystein Fodstad; Guangyu Zhang; Rajeev Samant; Lalita Shevde; Yaguang Xi; Lewis K. Pannell; Adam I. Riker (Clinical & Experimental Metastasis, 2009)

Diffusion Studies of Nanometer Polymersomes Across Tissue Engineered Human Oral Mucosa - Vanessa Hearnden; Hannah Lomas; Sheila MacNeil; Martin Thornhill; Craig Murdoch; Andrew Lewis; Jeppe Madsen; Adam Blanazs; Steve Armes; Giuseppe Battaglia (Pharmaceutical Research, 2009)

Establishing Representative No‐Take Areas in the Great Barrier Reef: Large‐Scale Implementation of Theory on Marine Protected Areas - LEANNE FERNANDES; JON DAY; ADAM LEWIS; SUZANNE SLEGERS; BRIGID KERRIGAN; DAN BREEN; DARREN CAMERON; BELINDA JAGO; JAMES HALL; DAVE LOWE; JAMES INNES; JOHN TANZER; et al. (Conservation Biology, 2005)
The Great Barrier Reef Marine Park, an area almost the size of Japan, has a new network of no‐take areas that significantly improves the protection of biodiversity. The new marine park zoning implements, in a quantitative manner, many of the theoretical design principles discussed in the literature. For example, the new network of no‐take areas has at least 20% protection per “bioregion,” minimum levels of protection for all known habitats and special or unique features, and minimum sizes for no‐take areas of at least 10 or 20 km across at the smallest diameter. Overall, more than 33% of the Great Barrier Reef Marine Park is now in no‐take areas (previously 4.5%). The steps taken leading to this outcome were to clarify to the interested public why the existing level of protection was inadequate; detail the conservation objectives of establishing new no‐take areas; work with relevant and independent experts to define, and contribute to, the best scientific process to deliver on the objectives; describe the biodiversity (e.g., map bioregions); define operational principles needed to achieve the objectives; invite community input on all of the above; gather and layer the data gathered in round‐table discussions; report the degree of achievement of principles for various options of no‐take areas; and determine how to address negative impacts. Some of the key success factors in this case have global relevance and include focusing initial communication on the problem to be addressed; applying the precautionary principle; using independent experts; facilitating input to decision making; conducting extensive and participatory consultation; having an existing marine park that encompassed much of the ecosystem; having legislative power under federal law; developing high‐level support; ensuring agency priority and ownership; and being able to address the issue of displaced fishers.